Application of network analysis to investigate sex differences in interactive systems of eating‐disorder psychopathology. Issue 12 (14th October 2019) - Perko, Victoria L.; Forbush, Kelsie T.; Siew, Cynthia S. Q.; Tregarthen, Jenna P.
Abstract: Objective: Although men comprise 25% of persons with eating disorders (EDs), most research has focused on understanding EDs in women. The theoretical framework underlying common ED treatment has not been rigorously tested in men. The purpose of this study was to compare the interconnectivity among ED symptoms in men versus women. Method: Participants ( N = 1, 348; 50% men) were individuals with anorexia nervosa, bulimia nervosa, binge‐eating disorder, or other specified feeding or eating disorder who were users of Recovery Record, a smartphone app for monitoring ED symptoms. Participants were matched on age and duration of illness. Network analysis was used to create networks of symptoms for both sexes. Strength centrality, network stability, and bootstrapped centrality differences were tested. The network comparison test (NCT) was used to identify sex differences between networks. Key players analysis was used to compare fragmentation of each network. Results: For both sexes, items related to binge eating and restricting emerged as highest in strength centrality. The NCT identified significant differences global strength ( p = .03) but not network invariance ( p = .06) suggesting that although the structure of the networks was not statistically different, the strength of the connections within the network was greater for women. Key players analysis indicated that both networks were similarly disrupted when important nodes within the network were removed. Discussion: Findings suggested that there are more similarities than differences in networks of EDs in men and women. Results have important clinical implications by supporting theoretical underpinnings of cognitive‐behavioral models of EDs in both men and women.